(untitled) (Damascus University Journal for the economic and Political sciences, 2023)
The aim of this research is identifying the changes in Capital Adequacy Ratio (CAR) raised from implementation Expected Credit Loss under International Financial Reporting Standards \9 and related Central Bank of Syria Circulations, Especially Circulation # 4in 2019, by performing T Test- Paired Samples for CAR and its components, regulatory Capital and risk weighted financial Assets for traditional bank listed in Damascus Stock Exchange (DSE) for the period 2018 because the availability of data before implementation and after the transitions, it showed that there are significance changes in CAR and related components, since the banks used retain earnings to cover the increase in allowance for expected credit loss and modeling extra allowances related to balances with banks, deposit with banks, financial assets at amortized costs, financial assets through other comprehensive income (FAOCI), and increasing direct and indirect facilities allowance for expected credit loss.